Estudo taxonômico das espécies de Heterospilus Haliday, 1836 (Hymenoptera, Braconidae: Doryctinae) em área de cerrado do Estado de São Paulo - Santiago, Diogo Fernandes (Universidade Federal de São Carlos, 2017)
Taxonomy and systematics are fundamental Sciences for categorization, description of species and how they relate and are distributed throughout the planet. Hymenoptera parasitoids are considered as the major components of the vast majority of terrestrial ecosystems with approximately 20% of all insects, comprising the most common group of the order Hymenoptera. The species of Heterospilus Haliday were captured in the cerrado stricto sensu area at the Estação Ecológica de Itirapina, Brotas, SP, using Moericke traps for a period of two years, from July 2013 to September 2014. A total of 324 specimens were collected, Doryctinae being the most abundant subfamily, probably to the method of capture used, since most of its hosts are found together in the soil. The total abundance of the collected material was higher in the rainy season, probably due to climatic variation and variation in the availability of food resources. There are nine different species for the group of granulated vertex, eighteen with striated vertex and none with smooth vertex, totaling twenty-seven, representing 6.7% of the total of species described worldwide, which can be considered high compared to what has already been described. The Cerrado, despite being a highly deforested Biome, presented a large number of new species, with the most frequent that with striated vertex
Keywords: Taxonomia; Cerrado; Hymenoptera parasitoides; Heterospilus Haliday; CIENCIAS BIOLOGICAS::ECOLOGIA